Evaluation of indigenous botanicals against rice hispa (University Journal of Zoology, Rajshahi University, 2007)
Key words: Botanicals; rice hispa; Dicladispa armigera; seed kernel; leaf extracts Univ. j. zool. Rajshahi Univ. Vol.22, 2003. pp. 71-80